Determinants of premature membrane rupture among mothers receiving labor care at public hospitals in Northeast Ethiopia: an unmatched case-control study - Selamyhun Tadesse; Elsabeth Addisu; Muluken Amare Wudu; Melaku Ashagrie Belete; Tesfaye Birhane (Scientific Reports)
Abstract Premature rupture of membranes is responsible for increased perinatal mortality and neonatal morbidity. Therefore, identifying the determining factors is essential for minimizing its adverse impact. Despite the existence of this problem in the study area, there is a gap in identifying the factors affecting its occurrence. We investigate the determinants of premature membrane rupture among mothers receiving labor care at three public hospitals public hospitals in the Northeast Ethiopia, from December 1, 2022, to March 30, 2023. Unmatched case‒control study was conducted and a total of 353 participants (118 cases and 235 controls) receiving labor care were recruited. The data were collected using a face to face interview and card review, entered into EpiData 4.6 and analyzed using STATA version 17. As a result; previous caesarian section (AOR: 2.11; 95% CI: 1.05–4.23), history of abortion (AOR: 3.68; 95% CI: 1.70–7.94), history of premature membrane rupture (AOR: 3.89; 95% CI: 1.73–8.71), chronic cough (AOR: 4.23; 95% CI: 1.47–12.18), mid-upper arm circumference < 23 cm (AOR: 3.47; 95% CI: 1.53–7.84), suspected sepsis (AOR: 2.99; 95% CI: 1.25–1.99), and presence of urinary tract infection (AOR: 3.14; 95% CI: 1.50–6.60) were determinants of premature membrane rupture. These findings underscore previous history of C/S, abortion, PROM, presence of different infections and malnutrition are associated with the case. This highlighting the need for comprehensive prenatal care.